Benefits, Barriers and Applications of Information Communication Technology in Construction Industry: a Contemporary Study - T. G. Vasista, Dr; Abraham Abone, Mr (International Journal of Engineering and Technology, 2018)
In the construction industry there is a necessity for improving the construction efficiency through adopting innovative methods. Information and Communication Technologies (ICT) help in increasing the client satisfaction reduce coordination errors and provide a greater understanding among project participants in terms of better handling issues and requirements. Better efficiency can be achieved by making a building smarter. Construction projects are faced with many challenges that must not be ignored or underestimated. Some of the wicked problems and challenges such as understanding how one decision will impact decisions in other areas; problem of addressing the risk due to dynamic and uncertainty existing in the environment; resolving conflict where there are competing claims resulting both good and bad outcomes from the same value system are required to be well managed, if required using innovative methods such as using ICT and software packages. Therefore Objective of this research is to explore and describe the use and applications of information and communication technologies in construction industry. It involves examining the current trends of ICT based construction practices and also to assess the potential for its improvement by way of innovation. In this the journey started with describing what innovative methodologies are required to be considered to drive the discussion of adopting and using ICT to handle the wicked problems in construction industry. Two rationalities are considered as a basis for working on ICT applications in construction management viz.: (i) Six stages of Project Life cycle management and (ii) Nine project management knowledge areas as described by PMI.Â Â